HUMANISTIC SUPERVISION MODEL IN IMPROVING THE PROFESSIONALISM OF ELEMENTARY SCHOOL TEACHERS IN THE ERA OF INDEPENDENT LEARNING - Suhardi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to analyze the implementation of humanistic supervision and its impact on improving the professionalism of elementary school teachers in the era of Independent Learning. The research uses a qualitative approach with a case study design carried out in one of the public elementary schools that has implemented Merdeka Belajar. The subjects of the study included the principal, the school supervisor, and 15 teachers as participants, which were determined through purposive sampling. Data were collected through participatory observation, in-depth interviews, and documentation studies, then analyzed using Miles, Huberman, & Saldaña's interactive model that included data reduction, data presentation, and conclusion drawn. The results of the study showed that humanistic supervision was carried out collaboratively and reflectively, through classroom visits, reflective discussions, and individual coaching that emphasized appreciation for teachers. This model has a positive impact on teacher professionalism, characterized by increased pedagogic skills, learning creativity, and teacher motivation and self-reflection. Despite the challenges of time constraints and lack of supervisor training, the implementation of humanistic supervision is supported by the school's Independent Learning policy and collaborative culture. This study concludes that humanistic supervision is effective as a strategy for fostering elementary school teachers in improving professionalism in the era of Independent Learning. These findings are expected to be a reference for school principals and supervisors in developing humanist supervision and empowering teachers.